Depth-adjustable ploughing roller for land preparation machine - ZHUANG ZHIYANG; CAO XUEHUA; WANG LIMEI; XUAN LIXIA (2023)
The utility model discloses a depth-adjustable plowing roller for a land preparation machine, which relates to the technical field of agricultural devices, and comprises two lower brackets, two upper brackets and a plowing roller, the opposite sides of the two lower brackets are provided with sliding holes, one side of each sliding hole is communicated with a plurality of mounting holes, the upper and lower sides of each mounting hole are provided with fixing holes, and the upper and lower sides of the mounting holes are communicated with the plowing roller. A rotating shaft fixedly penetrates through the center of the ploughing roller, the front end and the rear end of the rotating shaft are connected with the corresponding mounting holes in a penetrating mode, the outer wall of the rotating shaft is fixedly sleeved with two bearings, the outer walls of the bearings are fixedly connected with two fixing plates, and the two fixing plates are connected with the corresponding fixing holes in a penetrating mode